2007
DOI: 10.1177/00343552070500030101
|View full text |Cite
|
Sign up to set email alerts
|

Urban Youth With Disabilities

Abstract: Although postsecondary employment outcomes for transition-age youth with disabilities have improved over the past decade, minority youth with disabilities continue to lag behind their peers in achieving a job. This study of predominantly minority youth participating in the Marriott Foundation's Bridges From School to Work Program from 2000 to 2005 analyzed data for 4,571 urban youth to determine what factors are associated with securing employment, and the nature of the jobs that are secured. Findings indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 24 publications
3
31
1
Order By: Relevance
“…Successful job placement is defined as obtaining a job either part-or full-time during the participants' tenure at Bridges Program. In this sample, 76.6% of students secured a job, a rate consistent with prior studies of the Bridges database (Fabian, 2007;Gold et al, 2013). The highest job placement rate was Dallas (83.1%), and the lowest rate was Los Angeles (67.8%).…”
Section: Variables and Measures In The Studysupporting
confidence: 83%
See 1 more Smart Citation
“…Successful job placement is defined as obtaining a job either part-or full-time during the participants' tenure at Bridges Program. In this sample, 76.6% of students secured a job, a rate consistent with prior studies of the Bridges database (Fabian, 2007;Gold et al, 2013). The highest job placement rate was Dallas (83.1%), and the lowest rate was Los Angeles (67.8%).…”
Section: Variables and Measures In The Studysupporting
confidence: 83%
“…Not surprisingly, these variables have emerged in the majority of studies examining employment outcomes for transitioning youth. For example, Fabian (2007), and Gold et al (2013) consistently found that women participating in the Bridges Program were less likely to secure a job than young men, as did Newman et al (2009) in their analyses of NLTS-2 data. In their analysis, men earned significantly more per hour than did women, as did those with less significant disabilities, similar to the findings of the current study.…”
Section: Discussionmentioning
confidence: 72%
“…Other studies of the Bridges Program (Fabian, 2007;Luecking & Fabian, 2000) found that having a paid competitive job during high school was the strongest predictor of postschool jobs for this population. The current study, with its evidence of the high probability of predominantly minority youth being able to secure jobs with assistance, solidifies the basis for persuading school systems to apply resources to support "real" jobs in the community for youth with disabilities.…”
Section: Discussionmentioning
confidence: 68%
“…Table 2 presents job placement rates as a function of site, and the a priori selected predictors. Aggregated across the seven sites and the six program years (2006 through 2011), participants' overall job placement rate is 77.2% (n = 4,511 of 5,847), a proportion considerably higher compared with the 68% rate reported by Fabian (2007) for program participants aggregated across the 5 years prior to the period of this study (2000)(2001)(2002)(2003)(2004)(2005). Job placement rates exceeded 70% at all seven sites, ranging from a low at Chicago (71.6%) to a high at Dallas (85.5%).…”
Section: Research Questionmentioning
confidence: 83%
See 1 more Smart Citation